Efficacy of Transforaminal Epidural Steroid Injection with Local Anesthetic and Ozone Versus Transforaminal Epidural Steroid Injection with Local Anesthetic in Patients with Lumbar Radiculopathy - Mehmood, Tariq; Iqbal, Muhammad Rashid; Ranjha, Chaudhry Raheel; Iqbal, Mudassar; Ali, Aijaz; Zaid, Ameer Yaseer (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the efficacy of Transforaminal Epidural Steroid Injection with local anesthetic versus Transforaminal Epidural Steroid Injection with local anesthetic and Ozone in patients with lumbar spine radiculopathy. Study Design: Quasi-experimental study. Place and Duration of Study: Pain Management Centre, Department of Anesthesia, Combined Military Hospital Rawalpindi, Pakistan from Oct 2022- Mar 2023. Methodology: A total of 412 patients who underwent interventional procedures for radiculopathy were included in the study. These patients were divided into two equal groups, group-A (n=206) received Transforaminal Epidural Steroid Injection (40mg Triamcinolone) with local anesthetic (20mg Lignocaine) and Ozone (30 µg/ml) and group-B (n=206) received Transforaminal Epidural Steroid Injection (40mg Triamcinolone) with local anesthetic (20mg Lignocaine). The effects of both the regimens to treat pain in lower back were observed in the groups. Patients were assessed for pain using the visual analogue scale (VAS), for disability ..... Results: VAS at pre-procedure was 7.96 ± 0.587 and 8.15 ± 0.615 for group-A and B respectively (p= 0.005) and then at six months was 3.06 ± 0.898 for group-A and 3.45 ± 1.075 for group-B (p=0.001). Similarly, ODI at pre-procedure was 29.95 ± 4.032 and 30.06±3.761 for group-A and B respectively (p< 0.001) and then at six months was 13.83 ± 2.345 for group-A and 14.65± 2.336 for .... Conclusion: Lumbar Radiculopathy treated with Transforaminal Epidural Steroid Injection with local anesthetic and Ozone has more patient satisfac......